Encouraging reflective practice in the teacher education practicum: A dean’s early efforts - Fuentealba Jara, Rodrigo; Russell, Tom (Frontiers in Education, 2023)
This article presents an analysis of Rodrigo’s efforts in his first year as Dean to encourage reflective practice in the teacher education practicum, in consultation with Tom in the role of critical friend. The focus is on the importance of listening and the identification of assumptions underlying practices. The authors met in 2010 in a week-long seminar focused on the practicum in teacher education programs at a university in Santiago, Chile. A long conversation over dinner one evening revealed a significant interest in each other’s perspectives and experiences. Since that time, more than 20 opportunities to visit each other in Chile and in Canada have established an on-going connection for sharing insights as they emerge from experiences in each other’s country. The authors now consider themselves to be critical friends for the foreseeable future. In April 2021, Rodrigo was appointed as Dean of Education at Universidad Autónoma in Santiago, with an early focus on encouraging reflective practice by all who are involved in the teacher education practicum—student teachers, mentor teachers and faculty supervisors. Although Tom retired in 2019 after 42 years in teacher education practice and research at Queen’s University, he continues to explore the complex issue of how people learn to teach.